N05 Highlighting the critical contributions of Inflammatory Bowel Disease nurses in Canada: Perspectives from nurses, gastroenterologists, individuals living with IBD, and caregivers. (30th January 2023) - Rohatinsky, N; Zelinsky, S; Chauhan, U; Currie, B; Frost, K; Kroeker, K; Ma, C; Murray, K
Abstract: Background: Multidisciplinary teams are essential in managing Inflammatory Bowel Disease (IBD). IBD nurses play a critical role in improving patient outcomes and providing cost-effective quality of care. In Canada, access to IBD nurses remain inconsistent. There are more than 270, 000 people living with IBD in Canada and fewer than 90 IBD nurses to care for them. This study was conducted to capture the value of IBD nurses, to identify gaps in resources, and to generate strategies for building IBD nurse capacity and enhancing the contributions of IBD nurses in Canada. Methods: A convergent mixed-methods design was utilized to gather input from 4 stakeholder groups: IBD nurses, gastroenterologists, individuals living with IBD, and caregivers. Data collection was done through completing a review of the literature, stakeholder surveys, and one-on-one online semi-structured interviews with all stakeholders. Descriptive statistics were used for the quantitative analysis. Semi-structured interviews were audio recorded and transcribed verbatim then thematically analyzed. Results: The IBD nurse's role in clinical care was recognized as a value-add across all stakeholder groups. Having access to a specialized IBD nurse was recognized as a service that elevates the quality and continuity of patient care. As the interface between patients and other healthcare providers, there was recognition amongst stakeholders that IBD nurses are ideally positioned to educate patients about IBD management, general health promotion in the context of chronic disease and may support other aspects of care such as psychosocial, nutrition, and other extraintestinal manifestations or to help guide patients toward appropriate care channels. Many IBD nurses view advocacy as a logical extension of their official responsibilities, helping IBD patients to make treatment decisions and assisting them with disease challenges that affect their quality of life. Conclusion: IBD nurses represent an underused resource in Canadian IBD care. Canada currently falls short of the recommended 2.5 full-time IBD nurse equivalents per 250, 000 population. Achieving this objective will require a commitment to train IBD nurses and additional funding for their education and employment. The government can work with nursing institutions to set benchmarks, establish training programs, and create opportunities for IBD nurses in Canada. Introducing more IBD nurses into the system and using them to their full capacity makes sense from both a clinical and economic standpoint. It lifts the burden on gastroenterologists and primary care physicians, reduces costs to health systems while improving the overall quality of care for IBD patients.